UTILIZING THE SEESAW APPLICATION AS A PORTFOLIO REPORTING MEDIA IN INCREASING DIGITAL LITERACY FOR PAUD TEACHERS IN TELUKJAMBE BARAT DISTRICT, KARAWANG DISTRICT - Gitawidya Amalia Nurbidayah; Pujiarto Pujiarto; Kurniasih Kurniasih; Sri Fitri Yuningsih; Yani Suryani; Ika Puspitasari; Sri Purwati; Ratna Ahsanty (International Conferences on Early Childhood Education Proceedings, 2023)
In the period of early childhood development, attention is mainly given to the process of how children go through each stage of development and the achievements of all aspects of development according to their age. With the entry of the digitalization era in all aspects, educators must be able to use it, one of which is as a media for digital portfolio reporting which is also a communicating media about the achievement of children's development targets in class so that further stimulation can be carried out at home by parents. The purpose of this research is to evaluate the extent to which the Seesaw application can be used as a digital portfolios report and how it has an impact on increasing teachers' abilities in digital literacy. This study aims to gain a better understanding of how the use of the Seesaw application as a media for portfolio reporting has an impact on the digital literacy of PAUD teachers in Telukjambe Barat District, Karawang Regency. This research uses mixed methods, which combines quantitative and qualitative methods. This research shows that using the Seesaw application as a digital portfolios report can significantly increase digital literacy for PAUD teachers. This latest research found that simultaneous training and mentoring had a positive effect on improving teaching quality, the relationship between parents and teachers, and stimulating teachers' curiosity in exploring learning resources through digital devices. All teachers agree that digital portfolios are very important and useful to support learning processes and approaches in schools that can be communicated with parents at home. The increase in the second variable research after the intervention resulted 129.15 on the TCR average, or an increase of 51.66 percent compared to before the intervention.